2000
DOI: 10.1176/appi.ps.51.7.885
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Discharge Planning and Compliance With Outpatient Appointments on Readmission Rates

Abstract: Patients who did not have an outpatient appointment after discharge were two times more likely to be rehospitalized in the same year than patients who kept at least one outpatient appointment. Aggregated annual rates indicated that patients who kept appointments had a one in ten chance of being rehospitalized, whereas those who did not had a one in four chance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
167
2
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(175 citation statements)
references
References 12 publications
3
167
2
3
Order By: Relevance
“…[34][35][36][37] Our study design allowed examination of predictors of compliance without confounding by non-comprehension, in contrast with recent studies conducted among hospital inpatients. 1,29 Our results suggest that increased comprehension may not improve compliance for all patients.…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36][37] Our study design allowed examination of predictors of compliance without confounding by non-comprehension, in contrast with recent studies conducted among hospital inpatients. 1,29 Our results suggest that increased comprehension may not improve compliance for all patients.…”
Section: Discussionmentioning
confidence: 99%
“…[115][116][117][118] Repeat hospitalisation may be a result of one or a combination of several factors including (but not limited to) quality of care during previous hospitalisation (including early discharge), comprehensive discharge planning, 119 primary and community care after discharge (including outpatient follow-up) 120 and the patients' own social support systems and health behaviours. Therefore, repeat hospitalisation is an important indicator of the quality-of-care co-ordination between hospital care, primary care and community care settings.…”
Section: Doi: 103310/hsdr04260 Health Services and Delivery Researchmentioning
confidence: 99%
“…CMS has acknowledged this, and in their proposed rule, Reform of Requirements for Long-Term Care Facilities ( § 483. 20), recommend that in addition to documentation of the transition and/or discharge from nursing facilities, specific patient information be exchanged with the receiving provider (e.g., PCP). 17 However, they do not further specify how the communication should occur or require a specific format.…”
Section: Policy Implications and Future Researchmentioning
confidence: 99%
“…Evidence has shown that patients who follow up promptly with their PCPs after a hospitalization have improved outcomes, including fewer medication errors. [20][21][22][23] In an effort to reduce length of stay (LOS) and adverse events in the hospital, SNF physicians are being asked to provide care for more acutely ill patients. 24 Essentially, SNFs are becoming stepdown hospitals.…”
Section: Responsibilitiesmentioning
confidence: 99%